Formação permanente de professores: criticidade e reflexividade na perspectiva das ruralidades como espaços conectivos - Gelocha, Elizandra Aparecida Nascimento (2021)
Rural education has been a challenge for managers and teachers, as the school, as a space for transfo rmation, requires a theoretical practical and political position to be understood as an educational project. It is necessary to think of the rural school as a network, as an articulated system, with proposals and demands for valuing the countryside, agricu lture and the farming profession. Therefore, it is necessary to think about training proposals that take into account the cultural, social and regional diversity of the country and provide opportunities for reflection on historical critical and emancipator y pedagogical actions. After reflecting on the exposed situations, this thesis proposes Education with the Countryside, that is, a permanent training of educators and students, focused on the autonomy of both. With this in mind, the general objective was t o investigate the repercussions of ruralities in schools in the municipality of Quevedos, Rio Grande do Sul, in order to understand their implications for the process of permanent teacher training. The secretary of education of the municipality of Quevedos , three directors and two supervisors, referred to as interlocutors co authors, participated in the research. The methodology used had a qualitative approach. In the methodological context, Investigative formative Dialogical Circles were carried out, an ep istemological political proposal that has been worked on by the Dialogus Group (UFSM), which enables dialogue with teachers taking into account reality, their knowledge, their concerns, curiosities and questions. The Investigative Formative Dialogic Circles had two movements: one aimed at interlocutors co authors, and another directed at all teachers in the city network. In the political, epistemological and methodological perspective of Dialogical Circles, adopted in the research, there is no data collectio n or results to be analyzed, but interpretive comprehensive constructs where knowledge and bibliographies about the theme intertwined in spiral movements and were being (re)created following actions and self(trans)formations. The intentions expressed in th is study, based on the principles of Freire’s conception of education, pointed out the limits and possibilities faced by the interlocutors co authors during the dialogic process of ongoing training. The final considerations point to the understanding of Ed ucation with the Countryside in relation to the demands of reality, while taking into account the relationships established in the macro social context. The permanent training with teachers must be permeated by criticality and reflexivity in the perspectiv e of ruralities as connecting spaces, namely, multiple universes, neither superior nor inferior to the city space, but interdependent scientific and cultural spaces, times and movements, which are interconnected to history, politics, economics and contempo raneity, considering the teaching and the singular and plural realities of its subjects. Therefore, we signal the need to defend studies of a social, economic and political character on education, which value and guarantee everyone critical conditions, con sidering the students' particularities in order to provide continuous advancement in the expansion of knowledge. We hope that the commitment to teaching, hope and sharing can foster the desire to build pedagogical practices articulated to the needs of each group, thus bringing respect to differences and strengthening liberating education.